Financial And Macroeconomic Performance Effect On Net Interest Margins At Conventional Commercial Banks In Indonesia - Soeharjoto Soeharjoto; Debbie Aryani Tribudhi; Husna Leila Yusran; Lalu Masyhudi (Politeknik APP Jakarta, 2023)
Banking is an intermediary institution that serves as the driving force of development in Indonesia. Sustainability this institutions depends on the profit derived from Net Interest Margin. However, in its development, bank is influenced by internal performance and macroeconomic conditions. Aims of this study is to determine influence of financial and macroeconomic performance on Net Interest Margin in conventional banking in Indonesia. Net Interest Margin used as dependent variable and Operating Expenses and Operating Income, Loan to Deposit Ratio, interest rates, exchange rates as independent variable. Used regression method, and monthly time series data form financial services authority in 2017-2020. Loan to Deposit Ratio and interest rate have a positive and significant effect on Net Interest Margin while the exchange rate has a negative and significant effect to Net Interest Margin. However, Operating Expenses and Operating Income have not been shown to affect Net Interest Margin. If Banking performance improves, stable macroeconomic conditions, and regulations that support the banking sector, the Net Interest Margin conditions can be conducive